Literature Review: Pengaruh Kompres Kayu Manis Terhadap Penurunan Nyeri Artritis Gout Pada Lansia - Fauzi, Muhammad Nur; Krishna , Lucia Firsty Puspita (Neolectura, 2026)
Gout arthritis is a degenerative disease that affects the joint system and is characterized by the accumulation of uric acid crystals, which trigger inflammatory processes. This condition causes symptoms such as swelling, redness, and pain in several parts of the body. In addition to pharmacological therapy, non-pharmacological interventions such as warm cinnamon compresses may be used to help reduce pain complaints. This study aimed to determine the benefits of warm cinnamon compresses in reducing pain intensity among patients with gout arthritis. The research method employed was a literature review of five scientific articles obtained through a systematic search of Google Scholar and ResearchGate based on predetermined inclusion and exclusion criteria. The review results indicated that all analyzed articles reported a reduction in pain intensity, from severe to mild pain, following the application of cinnamon compresses in elderly patients with gout arthritis. In conclusion, warm cinnamon compresses have an effect on reducing pain in elderly individuals with gout arthritis.